2019
DOI: 10.1002/ijc.32103
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA ST3Gal6‐AS1/ST3Gal6 axis mediates colorectal cancer progression by regulating α‐2,3 sialylation via PI3K/Akt signaling

Abstract: Sialylation is associated with cancer progression. Long noncoding RNAs (lncRNAs) have important roles in diverse diseases including cancer. The lncRNA ST3Gal6 antisense 1 (ST3Gal6‐AS1) derives from the promoter region of sialyltransferase ST3Gal6. However, the mechanisms by which ST3Gal6‐AS1 modulates colorectal cancer (CRC) development through sialylation remain largely unknown. Here, we found that ST3Gal6‐AS1 and ST3Gal6 levels were lower in tumor tissues than adjacent normal tissues of CRC patients. The cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 32 publications
0
45
2
Order By: Relevance
“…The overexpression of ST3GAL6 has been reported in multiple cancers, such as breast cancer, multiple myeloma and hepatocellular carcinoma, whereas low expression level in their normal counterparts 43 - 45 . Dysregulation of ST3GAL6 promoted hepatocellular carcinoma and colon cancer cell proliferation and invasion via PI3K/AKT signaling, enhanced homing and survival of multiple myeloma in bone marrow niche 45 , 46 . Forced expression of ST3GAL6 also increased the resistance of gastric cancer cells to a Met tyrosine kinase receptor inhibitor crizotinib, with the compensatory activation of insulin receptor 47 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overexpression of ST3GAL6 has been reported in multiple cancers, such as breast cancer, multiple myeloma and hepatocellular carcinoma, whereas low expression level in their normal counterparts 43 - 45 . Dysregulation of ST3GAL6 promoted hepatocellular carcinoma and colon cancer cell proliferation and invasion via PI3K/AKT signaling, enhanced homing and survival of multiple myeloma in bone marrow niche 45 , 46 . Forced expression of ST3GAL6 also increased the resistance of gastric cancer cells to a Met tyrosine kinase receptor inhibitor crizotinib, with the compensatory activation of insulin receptor 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Under hypoxic or inflammatory conditions, stabilized HIF1α and IL6 or IL8 induced ST3GAL6 at transcriptional level in MDA-MB-231 and human bronchial mucosa cells, respectively 49 . LncRNA ST3GAL6-AS1, overlapping with ST3GAL6 at genomic level, positively regulated its host gene ST3GAL6 by recruiting MLL1 protein to enhance H3K4me3 level at ST3GAL6 promoter region 46 . In addition, ST3GAL6 could also be regulated by non-coding RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…KEGG pathway analysis indicated that the three lncRNAs' functions were potentially associated with several cancer-related pathways, such as the “PI3K-Akt signaling pathway,” “TGF-β signaling pathway,” “Colorectal cancer,” and “P53 signaling pathway.” Current studies have shown that the PI3K-Akt pathway is activated in many types of cancers. Many studies have indicated that the PI3K-Akt pathway plays a vital role in cell proliferation, migration, and invasion in CRC (35, 44, 45). Meanwhile, several studies have indicated that the TGF-β signaling pathway was also associated with lncRNAs; for example, the lncRNA SNHG6 could accelerate cell growth, invasion, and migration via activating the TGF-β signaling pathway in CRC (46).…”
Section: Discussionmentioning
confidence: 99%
“…ChIP has been used to detect the H3K4me3 signal in the promoter region of ST3Gal6, and knockout of ST3Gal6-AS1 affects the accumulation of H3K4me3. Bioinformatics analysis and RIP experiments have indicated that lncRNA ST3Gal6-AS1 binds histone methyltransferase MLL1, recruits it to the promoter region of ST3Gal6, and induces H3K4me3 modification, which in turn activates ST3Gal6 transcription (Figure 2C) [31]. Furthermore, the highly expressed lincRNA FEZF1-AS1 has been identified in gastric cancer.…”
Section: Lncrnas Are Involved In Regulating Histone Modificationsmentioning
confidence: 99%